Analysis of Cloud Computing and Its Challenges - Rajakumari, S. Edel Josephine; Bai, T. Daisy Premila; Leena, H.M (International Journal of Computer Sciences and Engineering, 2018)
Cloud Computing is a new paradigm that offers computing resources such as network, storage, servers, applications and services whenever there is a demand based on pay-as-you go standard. It is about sharing of resources among cloud customers. Cloud provides computing infrastructure with a development platform on which users can develop their own applications. Besides the advantages of Cloud, it has certain challenges to be resolved. In this article, the challenges of Cloud computing in various aspects are discussed.